Development of a Vessel Organ Culture System: Characterisation of the Method and Implications for the Reduction of Animal Experiments. Issue 4 (September 2013) - Zaniboni, Andrea; Zannoni, Augusta; Bernardini, Chiara; De Cecco, Marco; Bombardi, Cristiano; Seren, Eraldo; Forni, Monica; Bacci, Maria L.
In the field of cardiovascular research, the pig is considered to be an excellent animal model of human diseases. It is well-known that primary cultures of endothelial cells (ECs) are a powerful tool for the study of vascular physiology and pathology, and, according to the principles of the Three Rs, their use results in a substantial reduction in the numbers of experimental animals required. However, a limitation of EC culture is that the cells are not in their physiological context. Here, we describe and characterise a method for the culture of porcine vessels that overcomes the limitation of EC cultures, with the advantage of reducing the number of animals used for research purposes. The organ cultures were set-up by using an aortic cylinder obtained from the arteries of control pigs sacrificed for other experimental purposes. In order to characterise the method, vascular endothelial growth factor (VEGF) secretion, matrix metalloproteinase (MMP) activation and the vessel's structural features were evaluated during organ culture. These analyses confirm that the culture of aortic cylinder lumen, in a medium specific for ECs, results in a stable system in terms of VEGF and MMP secretion. The ECs do not undergo cell division during the organ culture, which is also the case in vivo, if no stimulation occurs. Overall, we show that this novel system closely resembles the in vivo context. Importantly, porcine aortas can be collected from either veterinary surgeries or slaughterhouses, without having to sacrifice animals specifically for the purposes of this type of research.